The development of a bacterial biosensor for the analysis of benzene in workplace air - Lanyon, Yvonne H. (Cranfield University, 2004)
The presence of toxic volatile organic compounds (VOCs) such as benzene in workplace air has accounted for the death of many occupationally exposed workers over the last century. The conventional gas chromatographic method of monitoring benzene is known to be costly, complex and in most cases, laboratory-based. Therefore a need exists for the development of low-cost, easy to use, portable devices that can be used on-site for the rapid evaluation of airborne benzene. In this thesis, the development of an amperometric bacterial biosensor based on Pseudomonas putida ML2 for the detection of airborne benzene is described. Benzene can be used by the bacteria as a sole carbon source, and its aerobic degradation can be measured using a dissolved oxygen electrode. In this work, P. putida ML2 cells were immobilised between two cellulose acetate membranes and fixed onto a Clark dissolved oxygen electrode. Biosensor responses were investigated in batch and kinetic (Flow Injection Analysis) mode, and also using screen-printed electrodes. In each case, the response characteristics, sensitivity, reproducibility and lifetime of the sensor were investigated, as well as construction techniques and operational parameters. The applicability of the biosensor for the analysis of air samples containing benzene was investigated. Air samples were collected from an exposure room of controlled concentration using charcoal adsorption tubes, and benzene extracted with solvent desorption using dimethylformamide (DMF). DMF proved to be compatible for use with the biosensor, causing minimal interference with the sensor response and causing no toxic effects on the bacterial cells. The biosensor displayed a linear detection range between 0.025 - 0.15 mM benzene based on standard solutions containing a maximum of 2% DMF, with a response time of 6 minutes. This linear detection range allowed the analysis of air containing between 3-16 ppm benzene, based on a 60-minute sampling period. The inter-assay reproducibility of the sensor response to standard benzene calibration curves under such conditions gave a 3% variation coefficient based on 5 separate assays (n = 17) using the same bacterial membrane. The FIA system was easily transported to an in situ location for the air sample analyses, and a correlation was obtained between the biosensor and gas chromatography (GC) results for the exposure room air samples investigated. Moreover, the biosensor displayed no interference to other benzene related compounds in the BTEX (benzene, toluene, ethylbenzene, xylene) range. Overall, this thesis has described the development of an alternative method for the monitoring of benzene in workplace air, using a bacterial biosensor based on Flow Injection Analysis. Advantages over the conventional GC methods including ease of operation, cost-effective production and portability demonstrate that the P. putida ML2 biosensor has potential applications as an alternative means for the rapid analysis of workplace air containing benzene.